2017
DOI: 10.1016/j.ymthe.2017.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Balance of Anti-CD123 Chimeric Antigen Receptor Binding Affinity and Density for the Targeting of Acute Myeloid Leukemia

Abstract: Chimeric antigen receptor (CAR)-redirected T lymphocytes are a promising immunotherapeutic approach and object of pre-clinical evaluation for the treatment of acute myeloid leukemia (AML). We developed a CAR against CD123, overexpressed on AML blasts and leukemic stem cells. However, potential recognition of low CD123-positive healthy tissues, through the on-target, off-tumor effect, limits safe clinical employment of CAR-redirected T cells. Therefore, we evaluated the effect of context-dependent variables cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
139
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(147 citation statements)
references
References 36 publications
7
139
1
Order By: Relevance
“…These “affinity‐tuned CARs” demonstrated minimal reactivity with healthy cells, while maintaining robust antitumor activity in murine models . Similarly promising results have been seen with CARs targeting ICAM‐1, CD38, and CD123 with micromolar‐range affinity, each of which exhibited improved ability to selectively kill antigen‐high target cells when compared to higher‐affinity counterparts which responded to antigen‐low targets as well …”
Section: Tumor Specificity and Car T Cell Logic Gatingmentioning
confidence: 80%
See 1 more Smart Citation
“…These “affinity‐tuned CARs” demonstrated minimal reactivity with healthy cells, while maintaining robust antitumor activity in murine models . Similarly promising results have been seen with CARs targeting ICAM‐1, CD38, and CD123 with micromolar‐range affinity, each of which exhibited improved ability to selectively kill antigen‐high target cells when compared to higher‐affinity counterparts which responded to antigen‐low targets as well …”
Section: Tumor Specificity and Car T Cell Logic Gatingmentioning
confidence: 80%
“…CAR T cells targeting the AML‐associated antigen folate receptor beta also demonstrated significantly improved in vitro and in vivo efficacy after a 20‐fold increase the affinity of the scFv . This principle has also been seen in TCRs targeting low site density pMHC; where increased TCR affinity allowed for enhanced responses against low antigen as long as affinity was low enough to allow for fast off‐rates and serial triggering, In contrast, a study of multiple affinity‐modified variants of a CD123 CAR demonstrated that neither increasing or decreasing the affinity of the CAR significantly altered the killing of target cells . Similarly, T cells engineered to express a high‐affinity variant of the CD22 CAR did not demonstrate improved efficacy against B‐ALL with low CD22 expression when compared to the standard affinity CD22 CAR .…”
Section: Antigen Low Escape and Car T Cell Activationmentioning
confidence: 97%
“…In the context of CD22-CARs, a comparison between two scFvs targeting the same epitope but with varying affinities did not reveal a significant impact of affinity on CAR function, whereas an alternative CD22 binder (m971) with lower affinity proved most efficacious, possibly because of better accessibility of the targeted epitope 34,35 . Thus, for a given antigen density on a target cell, there is likely to be an optimal range of scFv affinities and CAR expression levels required for a specific and effective antitumor response [36][37][38] .…”
Section: Review Articlementioning
confidence: 99%
“…Although targeting TAAs also expressed on normal tissues risks on-target, off-tumour toxicity, evidence from preclinical models suggests that CAR-T cells may not react to low-level antigen expression in healthy tissues 33,[36][37][38] . Instances of human epidermal growth factor receptor 2 (HER2)-CAR off-tumour toxicity 82 have been largely overshadowed by safe trials with a distinct HER2-CAR that demonstrated clinical efficacy in patients with sarcomas 91,92 .…”
Section: Nature Biomedical Engineeringmentioning
confidence: 99%
“…Preclinical data with T cells engineered with dual-signaling receptors demonstrated that the full T-cell activation is achieved in the presence of both antigens [88]. In this context, it is possible also to tune the scFv affinity of the CAR in order to balance the efficacy with the safety [89]. Notably, dual-signaling CAR or TanCAR showed enhanced anti-tumor activity as compared to the single CAR or pooling single CARs when both antigens were expressed by the tumor [79,90], highlighting both the efficacy and the safety concerns.…”
Section: Tumor Immune Escape: the Cd19 Antigen Loss Issuementioning
confidence: 99%